医学的適応症の治療 (2023)
本発明は、脳血管障害（ＣＶＡ）、特にＡＩＳに罹患しているヒト対象の治療に使用するための、アファメラノチド、ブレメラノチド、及びそれらの薬学的に許容できる塩などの、ｈＭＣ１Ｒ及びｈＭＣ４Ｒアゴニスト化合物に関する。【選択図】なし The present invention is directed to hMC1R and hMC4R agonist compounds such as afamelanotide, bremelanotide and pharmaceutically acceptable salts thereof for use in treatment of a human subject suffering from cerebrovascular accident (CVA), in particular AIS.